2019
DOI: 10.3389/fpsyg.2019.01129
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Expression and Eccentricity on Gaze Perception

Abstract: The perception of another’s gaze direction and facial expression complements verbal communication and modulates how we interact with other people. However, our perception of these two cues is not always accurate, even when we are looking directly at the person. In addition, in many cases social communication occurs within groups of people where we can’t always look directly at every person in the group. Here, we sought to examine how the presence of other people influences our perception of a target face. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…An a priori power analysis (G*Power 3; Faul et al, 2007 ) with a medium effect size of 0.25, a 1-β power of 0.80, and an alpha of 0.05 found that the required number of participants in the study should be 28. In addition, the sample size in similar studies has been restricted to 20–40 participants ( Ewbank et al, 2009 ; Pantelis and Kennedy, 2016 ; Lyyra et al, 2017 ; Awad et al, 2019 ). Thus, we expected to test 30 participants.…”
Section: Methodsmentioning
confidence: 99%
“…An a priori power analysis (G*Power 3; Faul et al, 2007 ) with a medium effect size of 0.25, a 1-β power of 0.80, and an alpha of 0.05 found that the required number of participants in the study should be 28. In addition, the sample size in similar studies has been restricted to 20–40 participants ( Ewbank et al, 2009 ; Pantelis and Kennedy, 2016 ; Lyyra et al, 2017 ; Awad et al, 2019 ). Thus, we expected to test 30 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Attentiveness (gaze) is also a crucial part of affect analysis, especially for people with communication disabilities [10]. Recent works showed a strong link between emotion recognition and eye gaze estimation [41], [42] which motivates us to use gaze to measure temporal expressiveness dynamics. Thus, we incorporate eye-gaze features in our algorithm by capturing gaze from the left eye and right eye.…”
Section: Methods a Motivation And Multimodal Facial Features Trackingmentioning
confidence: 99%
“…It is unclear whether this theory applies to group emotion processing as well. However, researchers have confirmed the consistency of the impact of familiar faces on the accuracy of facial perception at both individual and group levels (Awad et al, 2023; Bortolon et al, 2018). Besides, the limited resource would lead to inaccurate representations of individual expressions or coding only a fraction of the group's faces.…”
mentioning
confidence: 95%